Spirituality at Work and the Leadership Challenge (Keynote 3) - Gill, Roger (Journal for the Study of Spirituality, 2014)
Human beings have an animating need for meaning, purpose and a sense of value or worth in what they do. Many managers and employees — particularly those in industries in which the profit motive is commonplace — are seeking meaning in their work associated more closely with their personal values and beliefs or the need for personal fulfilment rather than just creating material wealth. This trend is reflected in a growing sense of spirituality in the workplace and, in turn, an increasing academic interest in workplace spirituality, spiritual intelligence and spiritual leadership. However, some managers view workplace spirituality with disdain; others have eagerly adopted it; and a few cynically regard it as another source of competitive advantage and rich ‘rewards’.The concept of spirituality at work has come to incorporate, transcend, or even to replace ‘religiousness’ with a secular humanist view that also involves looking inward at oneself. It is linked closely to the empowerment and engagement of people at work. Spiritual intelligence is needed for effective and ethical leadership. Spiritual leadership concerns creating or providing meaning, purpose and value for people based on a sense of shared vision, purpose, values and beliefs. The spiritual needs of people at work pose a growing challenge to those in leadership positions in business and in society. This article was first delivered as a keynote speech at the Third International Conference of the British Association for the Study of Spirituality, Spirituality in a Challenging World. Some of the content of the speech is not included in the article and additional material is provided.